Pengaruh Penggunaan Metode Point Counter Point Terhadap Keterampilan Menulis Teks Eksposisi Siswa Kelas X SMA N 1 Padang Sago - Putri A. Lestari (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2022)
This research is motivated by the students' skill in writing exposition text which is still low. This study has a purpose, namely the objectives of this study are as follows. First, it describes the writing skills of the tenth grade students of SMA N 1 Padang Sago before using the point counter point method. Second, it describes the writing skills of the tenth grade students of SMA N 1 Padang Sago after using the point counter point method. Third, describe the effect of using the point counter point method on the skills of writing expository texts for X grade students of SMA N 1 Padang Sago. This research method is Point Counter Point. The results of this study indicate that tcount 8.52 > ttable 1.71. The benefits of this research. First, for students of SMAN 1 X Padang Sago to train and motivate students to write exposition texts. Second, for Indonesian language teachers, as a teacher reference in using the point counter point method and as a teacher reference in encouraging students who are less interested in writing.